OPTIMIZATION OF THE PLACEMENT OF FAST-MOVING CATEGORY GOODS WITH THE PARETO ANALYSIS METHOD AT PT XYZ JAKARTA - Muhamad Firdaus Sastra Yuda; Luluk Fauziah (Antis Publisher, 2026)
Objective: PT XYZ Jakarta is a technology-based logistics company that provides end-to-end logistics solutions for business operators. One of the warehouses managed by PT XYZ stores a variety of client products with different movement characteristics, including fast-moving items. The main issue identified in the warehouse operations is inefficiency in the picking activity, which is caused by the randomized storage system that does not consider item demand frequency or the distance to the packing area. This condition results in increased picking time and the potential for daily distribution backlogs. This study aims to optimize the storage layout for fast-moving items by applying the Pareto method and the Time Motion Study approach to improve the efficiency of picking activities at PT XYZ Jakarta’s warehouse. Method: A descriptive qualitative method was employed in this research, with data collected through participatory observation, interviews, and documentation. The Pareto method was used to identify category A SKUs with high picking frequency, while the Time Motion Study was applied to measure and compare picking times between the existing layout and the proposed layout. Results: The findings show that the existing layout results in an average picking time of 5.12 minutes per SKU, whereas the proposed layout reduces the time to 3.7 minutes per SKU. This indicates an improvement in picking efficiency of approximately 41.8%, with productivity increasing from 12 to 17 SKUs per hour. Placing fast-moving items closer to the packing area has proven effective in reducing picker travel time and optimizing overall warehouse operational workflows. Novelty: The novelty of this study lies in the application of the Pareto method and the Time Motion Study approach to optimize the storage layout of fast-moving items in a warehouse, leading to a significant improvement in picking efficiency and overall warehouse operations. This method provides a systematic approach to addressing inefficiencies in warehouse management, with practical implications for logistics companies.